Sistem Pendukung Keputusan Kelayakan Inkubasi UMKM pada PT XYZ Menggunakan Metode TOPSIS - Raditya Putra Rasyidien; Mulyati Mulyati (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
PT XYZ is an institution or agency with an important role in carrying out government tasks in certain fields. One of the units owned by PT XYZ is an incubator unit that focuses on providing support to MSMEs to develop and improve their business competitiveness. However, in the process of selecting MSMEs that are eligible for the incubation program, there are still obstacles due to an assessment system that is not well structured. This causes difficulties in determining MSMEs that truly meet the criteria and have the potential to develop through the incubation program. One of these problems is the development of a Decision Support System (DSS) application to assist the process of selecting MSMEs that are eligible for incubation at PT XYZ. This application uses a straightforward, logical, and easy-to-understand decision-making method known as the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. By implementing this method, the system is expected to provide more objective and structured assessment results, so that it can increase efficiency in determining the MSMEs that have the most potential to be fostered through the incubation program at PT XYZ.